Word-Formation : an international handbook of the languages of Europe. - Müller, Peter O., 1955-; Ohnheiser, Ingeborg; Olsen, Susan, 1948-; Rainer, Franz, 1957- (Handbücher zur Sprach- und Kommunikationswissenschaft,, 2016)
This handbook comprises an in-depth presentation of the state of the art in word-formation. The five volumes contain 207 articles written by leading international scholars. The XVI chapters of the handbook provide the reader, in both general articles and individual studies, with a wide variety of perspectives: word-formation as a linguistic discipline (history of science, theoretical concepts), units and processes in word-formation, rules and restrictions, semantics and pragmatics, foreign word-formation, language planning and purism, historical word-formation, word-formation in language acquisition and aphasia, word-formation and language use, tools in word-formation research. The final chapter comprises 74 portraits of word-formation in the individual languages of Europe and offers an innovative perspective. These portraits afford the first overview of this kind and will prove useful for future typological research. This handbook will provide an essential reference for both advanced students and researchers in word-formation and related fields within linguistics.